Biotechnology in Malaria Management: A Case Study in a Semi-urban Nigerian Clinic - Kayode, Olaniyan O.; Wellington, Oyibo A.; C, Okangba (Covenant Journal of Physical and Life Sciences, 2015)
Until recently, in areas of high malaria transmission such as Nigeria, malaria treatment has been based mainly on clinical diagnosis which was presumptive, because malaria was considered one of the commonest causes of fever. With the availability of new tools such as parasite–based rapid diagnostic kits, a product of biotechnology, which complements the standard microscopy, it is imperative to provide targeted treatment on accurate estimation of true malaria cases. To proffer solution to the limitations of microscopy, this study was carried out to ascertain the reliability of SD Bioline HRP-2-Based RDTs in malaria case management. A parasite based diagnosis of malaria was carried out on the total 1,276 patients attending an out-clinic in a Semi-urban area (Amukoko) of Lagos State, South West Nigeria to evaluate specific performance characteristics of SD Bioline HRP-2 RDT in malaria case management using microscopy as a gold standard. Only 15.4% and 14.6% was positive for P. falciparum by HRP- 2-RDT (Rapid Diagnostic Testing) and microscopy respectively and the sensitivity, specificity, PPV and NPV are 94%, 98.5%, 91.4% and 98.2% respectively. Using RDT, fever has a sensitivity of 79.7% and specificity of 60.5%. Patients have fever but no HRP-2 in their blood (fever + Neg. RDT). Since symptoms of malaria are not only peculiar to P. falciparum infection, parasite based diagnosis must be performed. The performance characteristics of the SD Bioline HRP-2 RDT generated from this study indicated that the tool is reliable and fast in generating the test result. Similarly, parasite based diagnosis is required to eliminate other causes of fever symptoms. Key words: Malaria, Biotechnology, Microscopy, Case management.